Influencia de la hora de degustación en la percepción sensorial de yogur de leche de cabra a través de un Interfaz Cerebro-Computador - Guevara Caruajulca, Leidy Carina (2017)
The influence of the hour of tasting in the sensory perception (SP) of goat-milk-yogurt (GMY) through a device called brain-computer interface (BCI) was performed based on the sensory acceptability (SA) of GMY (fruity with lucuma 15% and 20% w/w) with 20 untrained panelists of both sexes and ages between 20 and 25. This analysis was performed in two segments: 10 am-12 pm and 4-6 pm, through a hedonic scale of 7 points and an electroencephalography (EEG) Emotiv Epoc (EE) helmet. The processing and quantification (at RGB scale) of panelists’ EEG (mental images) focused on the frontal part of the brain and the β brain waves, due to its implication on the perception and emotional regulation as it presents/displays greater activation of color (Red) during the SP. With the aim of “Principal Component Analysis” (PCA) it was determined by correlation variables that the SP of GMY is influenced by the hour of tasting and that the acceptance and emotional state of panelists are better discriminated in afternoon hours concluding that the best time for tasting in laboratory conditions of sensory analysis is in the range of 4-6 pm.